Integrating Worksite Smoking Cessation Services Into the Construction Sector: Opportunities and Challenges. (December 2019) - Asfar, Taghrid; McClure, Laura A.; Arheart, Kristopher L.; Ruano-Herreria, Estefania C.; Gilford, Clark G.; Moore, Kevin; Dietz, Noella A.; Ward, Kenneth D.; Lee, David J.; Caban-Martinez, Alberto J.
Background . Smoking prevalence among Hispanic/Latino construction workers in the United States is very high (31%). Aims. To investigate tobacco use profiles in these minority workers and explore their management's views about implementing sustainable worksite smoking cessation services. Methods. Analysis of baseline data from a smoking cessation trial among Hispanic/Latino construction workers ( n = 134; adult men ≥18 years), and semistructured, 45-minute interviews with 24 key personnel at six construction companies in south Florida were conducted. Interviews were recorded, transcribed, and analyzed thematically. Results . Overall, 43.3% of workers were Cuban, and 81.3% had low acculturation level. Nicotine dependence levels were "high" in 61.8% of workers. Half of the workers had a successful quit attempt but only 9.9% received advice from a physician to quit smoking, 16.7% used medication to quit, and 79.2% did not receive assistance. Participants in the interviews stated that nothing was provided to help smokers quit smoking and considered distributing self-help materials with free medications as the most appropriate service. Challenges to integrating the service were time restriction and cost. Recommendations for implementing the service were local/state government mandate. Discussion. Tailoring tobacco treatment to Hispanic/Latino construction workers' job circumstances and culture is essential to support their cessation efforts. Integrating worksite tobacco treatment services into other available health promotion programs (e.g., safety) and enforcing smoke-free legislation in the construction sector can facilitate its adoption. Conclusion . Involving key stakeholders and mandating the service by the State and local government are necessary to integrate sustainable worksite smoking cessation services in the construction sector.